State policy in the field of cybersecurity: international partnership as a tool for developing human resource potential of the civil service - Honcharuk, Yurii (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The theses consider the priorities of the state policy in the field of cybersecurity in the conditions of martial law and the latest threats of 2025–2026. It is substantiated that the human factor is a critical vulnerability that requires a transformation of approaches to the training of civil servants - from theory to practical cyber resilience. The role of international partnership and ENISA's experience in the development of human resource potential, as well as the implementation of the European Skills Framework (ECSF), is highlighted. The impact of artificial intelligence on cyberattacks and protective mechanisms, the feasibility of the Zero Trust strategy and the protection of software supply chains are analyzed. Ways to improve public administration through the harmonization of legislation with the NIS2 Directive and the implementation of ISO standards to strengthen national resilience are identified.